Isolation and identification of an alkaloidic compound similar to Calothrixin-A from green alga Cladophora crispata (Roth.) Kützing - Athbi, Ahmed M.; AL-Assedi, Eqbal J.; AL-Nassir, Areej F. (Iraqi Journal of Aquaculture, 2022)
The isolation and identification of an alkaloidic compound similar to Calothrixin-A for were done here first time from the green algae (Chlorophyta) Cladophora crispata, isolated from Garmat-Ali river in Basrah in Iraq, purified and cultivated in Chu-10 medium. The growth rate was K=1.3 and the generation time G=0.23. The identification of the compound was made depending on its chemical and physical properties by using thin layer chromatoghraphy (TLC) and column chromatoghraphy. A single compound was isolated and tested by University and IR spectra. The melting point and solubility of the purified compound were determined using organic and inorganic solvents. The minimal inhibitory concentration (MIC) value was 5.5 μg /cm3 against G-positive bacteria Staphylococcus aurrus (ATCC25922) and 6 μg/cm3 against G-negetive bacteria Escherichia coli (ATCC25923). The toxicity of the alkaloidic compound was examined against human red blood cells and no toxic effect was detected.